2012 20th IEEE International Requirements Engineering Conference (RE) 2012
DOI: 10.1109/re.2012.6345810
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of functional software requirements space: The law of requirements taxonomic growth

Abstract: This paper reports on a large-scale empirical multiple-case study that aimed to characterize the requirements space in the domain of web-based Enterprise Systems (ES). Results from this study, among others, showed that, on the average, about 85% of all the software functionalities in the studied domain are specified using a small core set of five requirements classes even though the results of the study hint at a larger set of nine requirements classes that should be covered. The study also uncovered a law des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…It has been argued in earlier studies that the solution approach to one type of system may not be applicable to another one whether the concern is related to requirements representation [6] or analysis [7,8] as the systems may range from mission-critical, safety critical applications to enterprise applications and Web-based systems to mobile applications. The last point presents an opportunity to validate one of the proposed requirements taxonomies by either strongly correlating the taxonomy under study to an established framework or by conducting an empirical study at a wide scale.In this chapter, we shall focus on the last point of validating the functional requirements taxonomy by considering one of the functional requirements classiication proposed earlier [9][10][11][12][13][14]. Though requirements are broadly classiied as functional and non-functional, the vital role played by requirements in the development of information systems motivated us to do an in-depth study of functional requirements.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…It has been argued in earlier studies that the solution approach to one type of system may not be applicable to another one whether the concern is related to requirements representation [6] or analysis [7,8] as the systems may range from mission-critical, safety critical applications to enterprise applications and Web-based systems to mobile applications. The last point presents an opportunity to validate one of the proposed requirements taxonomies by either strongly correlating the taxonomy under study to an established framework or by conducting an empirical study at a wide scale.In this chapter, we shall focus on the last point of validating the functional requirements taxonomy by considering one of the functional requirements classiication proposed earlier [9][10][11][12][13][14]. Though requirements are broadly classiied as functional and non-functional, the vital role played by requirements in the development of information systems motivated us to do an in-depth study of functional requirements.…”
mentioning
confidence: 99%
“…His study reveals 12 classes of functional requirements, namely: (1) data input, (2) data output, (3) data validation, (4) business logic, (5) data persistence, (6) communication, (7) event trigger, (8) user interface navigation, (9) user interface, (10) external call, (11) user interface logic and (12) (1) entity modelling requirements, (2) user interface requirements, (3) user privileges requirements, (4) user interaction requirements, (5) business worklow requirements, (6) business constraints requirements and (7) external communication requirements. Of these two available classiication schemes-by Ghazarian [12], and Sharma and Biswas [14]-we have selected the later one for our work because while studying these two schemes, we observed that the taxonomy of functional requirements as proposed by Ghazarian [12] is close to the solution domain (developed code) and not the problem domain (requirements speciication) of information systems. RE is the only phase of software development that deals with both the problem space and the solution space of the envisioned software system [18] as this phase only bridges the gap between 'as-is' system and the 'to-be' system.…”
mentioning
confidence: 99%
See 3 more Smart Citations